The Forgotten Marlins: A Tribute to the 1956-1960 Original Miami Marlins - Zygner, Sam (Rowman & Littlefield Publishers, 2013)
On April 4, 2012, the former Florida Marlins of Major League Baseball played their first official game under their new name—the Miami Marlins. Many in attendance were unaware, however, that the original Miami Marlins had played in their city more than 50 years earlier. As part of the AAA International League, the 1956 Marlins helped set the stage for major league baseball’s entry into south Florida. During the five years this minor league club played in Miami Stadium, fans were treated to their first taste of high level baseball, with a team made up of battle-hardened veterans and fresh up-and-comers. The Forgotten Marlins: A Tribute to the 1956-1960 Original Miami Marlins brings to life one of the most colorful and flamboyant teams to ever play in baseball’s minor leagues. During their five years of existence, the Marlins featured prominent personalities such as eccentric manager Pepper Martin, zany Mickey McDermott, maverick promoter Bill Veeck, and Hall-of-Famer Satchel Paige. Although the team was an instant sensation, drawing national attention with their outlandish promotions, success did not always follow. The Forgotten Marlins relives those days in detail and follows the players through their triumphs and tribulations both on and off the diamond. Including rarely-heard stories about baseball icon Satchel Paige’s years in Miami, and containing interviews between the author and several of the surviving ballplayers, this bookis a unique and comprehensive account of a truly original baseball team. The Forgotten Marlins is an entertaining and engaging read for all baseball fans and historians.